An analytical study of the atmospheric boundary‐layer flow and divergence over an SST front. (17th July 2019) - Ayet, Alex; Redelsperger, Jean‐Luc
Abstract : We present an analytical model reproducing literature‐based numerical simulations of the Marine Atmospheric Boundary Layer (MABL) over a Sea‐Surface Temperature (SST) front, with wind blowing from the cold to the warm side. Turbulence is parametrized through a varying diffusion coefficient with two critical features: it is parabolic in the vertical and its mean value is decoupled from the MABL height (unlike an Ekman layer model). These two novel features are found essential to recover the internal structure of the MABL from numerical simulations. Different dynamical regimes are obtained and interpreted through non‐dimensional numbers characterizing the relative importance of terms driving the momentum equation. A closed‐form expression of the vertically integrated wind divergence in the MABL is then obtained. The resulting divergence is linearly linked to the SST Laplacian and to the downwind SST gradient. This shows that the response of the MABL wind divergence to an SST front is highly dependent on its spatial scale. The coupling coefficients vary with the ratio of MABL height to turbulence strength, i.e. the inverse Ekman number. We further show different regimes in the rate of variation of the coupling coefficients, depending on the Ekman number value. This can result in qualitatively different vertical winds, having potential implications for the coupling of the MABL with the free troposphere. Abstract : Understanding how the atmospheric boundary layer responds to Sea Surface Temperature (SST) fronts is crucial for a number of applications. Here, this response is studied by means of an analytical model for a meridional front, as shown in the figure. The model allows us to define and explore a phase space of the different dynamical regimes occurring in the boundary layer. The depth‐integrated wind divergence is analytically computed and found to be linked to different derivatives of the SST field, depending on the dynamical regimes.